Raspberry ketone diet supplement reduces attraction of sterile male Queensland fruit fly to cuelure by altering expression of chemoreceptor genes - Mohammed Abul Monjur Khan (Nature Portfolio, 2021)
Abstract Sterile male Queensland fruit fly, Bactrocera tryoni (Froggatt), fed as immature adults on the plant compound raspberry ketone (RK), show a reduced attraction to cuelure, a synthetic analogue of RK used as an attractant in Male Annihilation Technique. We hypothesized the reduced attraction of RK-fed adult males to cuelure may be a consequence of altered expression of chemoreception genes. A Y-tube olfactometer assay with RK-fed and RK-unfed sterile B. tryoni males tested the subsequent behavioural response to cuelure. Behavioral assays confirmed a significant decrease in attraction of RK-fed sterile males to cuelure. RK-fed, non-responders (to cue-lure) and RK-unfed, responders (to cue-lure) males were sampled and gene expression compared by de novo RNA-seq analysis. A total of 269 genes in fly heads were differentially expressed between replicated groups of RK-fed, cuelure non-responders and RK-unfed, cuelure responders. Among them, 218 genes including 4 chemoreceptor genes were up regulated and 51 genes were down regulated in RK-fed, cuelure non-responders. De novo assembly generated many genes with unknown functions and no significant BLAST hits to homologues in other species. The enriched and suppressed genes reported here, shed light on the transcriptional changes that affect the dynamics of insect responses to chemical stimuli.